Trust formation based on subjective logic and PGP web-of-trust for information sharing in mobile ad-hoc network - Bakar A.A.; Ahmad A.R.; Manan J.-L.A.; Ismail R. (2023)
Trust play important roles in Mobile ad hoc networks since nodes may randomly joined and leave the network at their own pace. In catastrophe like massive accident or earthquake, groups of rescue personnel form a temporary network structure at the rescue site using their portable devices for coordinating the rescue relief. These groups of user from different agency need to use the temporary network for communication and also for sharing the information. Trust plays important roles in these groups since sharing of information must be among trusted and authorized nodes only. In this paper we form trust model adopting the PGP web-of-trust concept with subjective logic. The PGP web-of-trust is suitable method to adopt in mobile ad hoc networks since nodes are communicating based on peer to peer, hence peer recommendation can be use to create trust between peers. The use of subjective logic operators for calculating trust in the proposed trust model is appropriate since there is an element such as uncertainty as part of calculation. Uncertainty is important in this dynamic network since we do not have full information when decision is make. The trust value later is mapped with the access control policy to determine user access privileges. 2010 IEEE.